Treatment method of metal oxide layer-perovskite layer interface

By using a combination of ligand reagents and SAM materials in perovskite solar cells to form a ligand-coupled SAM layer, the problems of insufficient adhesion between the conductive substrate, metal oxide layer and SAM layer and insufficient self-assembly uniformity of the SAM layer are solved, and the charge transport characteristics of perovskite solar cells are significantly optimized.

CN119604164AActive Publication Date: 2025-03-11华能青海发电有限公司 +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411812312.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-11
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

In perovskite solar cells, the conductive substrate, metal oxide layer and SAM layer are easily delaminated, and the self-assembly uniformity of the SAM layer is insufficient, resulting in undesirable charge transport characteristics.

Method used

By mixing the ligand reagent and SAM material into the solvent, coating on the surface of the metal oxide layer, and annealing treatment, a ligand-coupled SAM layer is formed. This method uses ligand reagent to form hydrogen bonds with the conductive substrate and the metal oxide layer to enhance adhesion and improve self-assembly uniformity of the SAM layer.

Benefits of technology

The adhesion between the conductive substrate, metal oxide layer and SAM layer is improved, and the self-assembly uniformity of the SAM layer is enhanced, thereby optimizing the charge transport characteristics of perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005180837640000061
    Figure BDA0005180837640000061
Patent Text Reader

Abstract

The invention provides a metal oxide layer-perovskite layer interface processing method, and belongs to the technical field of perovskite solar cells. The treatment method comprises the following steps that S1, a ligand reagent and an SAM material are dissolved in a solvent, a mixed solution is obtained, and the ligand reagent comprises at least one of-OH groups,-COOH groups and-NH2 groups; s2, coating the surface of a metal oxide layer with the mixed solution to obtain a wet film; and S3, carrying out annealing treatment on the wet film to obtain the ligand coupling SAM layer. According to the processing method, ionic bonds and-OH groups and / or-COOH groups and / or-NH2 groups in the ligand reagent are formed through reaction of the ligand reagent and the SAM, a metal oxide layer-perovskite layer interface can be optimized, and the charge transfer characteristic of the perovskite solar cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite solar cells, and in particular relates to a method for processing a metal oxide layer-perovskite layer interface. Background Art

[0002] Perovskite solar cells are a revolutionary new photovoltaic technology, selected by the US magazine Science as one of the top ten global technological breakthroughs in 2013. They have the characteristics and advantages of high efficiency, low cost, and can be prepared by low-temperature solution method. After just over a decade of development, perovskite solar cells have become the hottest branch of next-generation photovoltaic technology, attracting great attention and R&D investment from domestic and foreign academic and industrial circles.

[0003] In recent years, as a new class of ultrathin materials, self-assembled monolayer (SAM) materials have been widely explored by researchers in academia and industry as they play a key role in various solution-processed thin-film electronic devices, including OFETs, PSCs, OSCs, and OLEDs. Due to their good structural versatility and ease of processing, SAMs can effectively passivate and optimize interfaces in solution-processed thin-film electronic devices, which is conducive to the fabrication of efficient, functional, large-size or flexible devices for complex circuits and integrated systems. In addition, their biocompatibility derived from the nature of organic matter provides new solutions for emerging fields, such as IoT sensors for wearable electronics and biomedical applications.

[0004] In the field of perovskite solar cells, there are also studies on using SAM as a hole transport layer. For example, patent application document CN118555884A discloses a method for optimizing the hole transport layer of NiOx / SAM in perovskite solar cells, which belongs to the technical field of preparation of perovskite solar cells. By improving the surface of NiOx film, uniform and robust anchoring of SAM molecules is achieved, thereby promoting charge extraction and inhibiting interface non-radiative recombination. The present invention mainly improves the surface properties of NiOx film by subjecting the surface of NiOx film to plasma treatment (O2-plasma) in an oxygen atmosphere; O2-plasma treatment increases the conductivity of NiOx and promotes hole extraction from perovskite to NiOx / SAM; SAM molecules form a uniform, dense and strong monolayer on the surface of NiOx treated with O2-plasma, achieving high-quality perovskite film and efficient charge extraction.

[0005] However, in the prior art, when preparing a perovskite layer on a SAM layer, stratification is easy to occur between the conductive substrate, the metal oxide layer, and the SAM layer, and the self-assembly uniformity of the SAM layer needs to be improved, resulting in the charge transfer characteristics of the perovskite solar cell being not good enough. Therefore, there is an urgent need to design a method for treating the interface of the metal oxide layer-perovskite layer, which can improve the adhesion between the conductive substrate, the metal oxide layer, and the SAM layer, and improve the self-assembly uniformity of the SAM layer, thereby achieving the purpose of optimizing the charge transfer characteristics of the perovskite solar cell. Summary of the invention

[0006] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, an embodiment of the present invention provides a method for treating the interface of a metal oxide layer-perovskite layer.

[0007] An embodiment of the present invention provides a method for processing a metal oxide layer-perovskite layer interface, comprising the following steps:

[0008] S1. dissolving a ligand reagent and a SAM material into a solvent to obtain a mixed solution, wherein the ligand reagent has at least one of an -OH group, a -COOH group and a -NH2 group;

[0009] S2. applying the mixed solution onto the surface of the metal oxide layer to obtain a wet film;

[0010] S3. Annealing the wet film to obtain a ligand-coupled SAM layer.

[0011] The advantages and technical effects brought by the processing method of the embodiment of the present invention are as follows:

[0012] (1) The ligand reagent and the SAM material are mixed and then coated on the surface of the metal oxide layer. The ligand reagent and the SAM material react to form ionic bonds, and the -OH group and / or -COOH group and / or -NH2 group in the ligand reagent can form hydrogen bonds with the conductive substrate and / or the metal oxide layer, thereby further strengthening the adhesion of the metal oxide layer to the conductive substrate and the adhesion of the ligand-coupled SAM layer to the metal oxide layer. This combination is beneficial for them to adhere to the conductive substrate during the subsequent processing of the perovskite layer.

[0013] (2) The ligand reagent has -OH groups and / or -COOH groups and / or -NH2 groups, which helps to improve the self-assembly uniformity of the ligand-coupled SAM layer.

[0014] (3) The ligand reagent has an -OH group and / or a -COOH group and / or a -NH2 group, which helps the ligand coupling SAM layer to react with the subsequently formed perovskite layer, thereby helping to form a two-dimensional perovskite layer under the three-dimensional perovskite layer, thereby improving the overall stability of the perovskite layer.

[0015] In some embodiments, the ligand agent is at least one of 4-(1H-1,2,4-triazol-1-yl)benzoic acid (Hbza), 3-(1H-1,2,4-triazol-1-yl)benzoic acid (3-Hbza) and thiol-polyethylene glycol-amino.

[0016] In some embodiments, the SAM material is at least one of 2PACz, Meo-2PACz, and Me-4PACz.

[0017] In some embodiments, the mass ratio of the ligand reagent to the SAM material is 1:3 to 3:1.

[0018] In some embodiments, the solvent is at least one of isopropanol, ethanol, and N,N-dimethylformamide.

[0019] In some embodiments, in the mixed solution, the concentration of the ligand reagent is 1-10 mg / mL.

[0020] In some embodiments, in the mixed solution, the concentration of the SAM material is 1-10 mg / mL.

[0021] In some embodiments, the holding temperature of the annealing treatment is 50-150° C., and the holding time of the annealing treatment is 1-30 min.

[0022] In some embodiments, the thickness of the ligand-coupled SAM layer is 10-30 nm. DETAILED DESCRIPTION

[0023] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0024] An embodiment of the present invention provides a method for processing a metal oxide layer-perovskite layer interface, comprising the following steps:

[0025] S1. dissolving a ligand reagent and a SAM material into a solvent to obtain a mixed solution, wherein the ligand reagent has at least one of an -OH group, a -COOH group and a -NH2 group;

[0026] S2. applying the mixed solution onto the surface of the metal oxide layer to obtain a wet film;

[0027] S3. Annealing the wet film to obtain a ligand-coupled SAM layer.

[0028] Working principle: The treatment method of the embodiment of the present invention mixes the ligand reagent and the SAM material, and then applies it on the surface of the metal oxide layer, and utilizes the reaction between the ligand reagent and the SAM material to form an ionic bond, and the -OH group and / or -COOH group and / or -NH2 group in the ligand reagent can form a hydrogen bond with the conductive substrate and / or the metal oxide layer, further strengthening the adhesion of the metal oxide layer to the conductive substrate and the adhesion of the ligand-coupled SAM layer to the metal oxide layer. This combination is conducive to their adhesion to the conductive substrate during the subsequent perovskite layer processing. In addition, the ligand reagent has an -OH group and / or a -COOH group and / or a -NH2 group, which helps to improve the self-assembly uniformity of the ligand-coupled SAM layer. In addition, the ligand reagent has an -OH group and / or a -COOH group and / or a -NH2 group, which helps the ligand-coupled SAM layer to react with the subsequently formed perovskite layer, thereby helping to form a two-dimensional perovskite layer below the three-dimensional perovskite layer, thereby improving the overall stability of the perovskite layer.

[0029] In some embodiments, the ligand reagent includes but is not limited to at least one of 4-(1H-1,2,4-triazol-1-yl)benzoic acid (Hbza), 3-(1H-1,2,4-triazol-1-yl)benzoic acid (3-Hbza) and thiol-polyethylene glycol-amino, etc. The above-listed ligand reagents have abundant -OH groups and / or -COOH groups and / or -NH2 groups, which are beneficial to optimize the interface between the metal oxide layer and the perovskite layer and improve the charge transfer characteristics of the perovskite solar cell.

[0030] In some embodiments, the SAM material includes but is not limited to at least one of 2PACz, Meo-2PACz, and Me-4PACz, etc. The SAM materials listed above can improve the uniformity and stability of the subsequently formed perovskite layer.

[0031] In some embodiments, the mass ratio of the ligand reagent to the SAM material is 1:3 to 3:1, such as 1:3, 1:2, 1:1, 2:1, 3:1, etc. When the mass ratio of the ligand reagent to the SAM material is too low, it is not conducive to improving the adhesion between the conductive substrate, the metal oxide layer and the ligand-coupled SAM layer, nor is it conducive to improving the self-assembly uniformity of the ligand-coupled SAM layer. When the mass ratio of the ligand reagent to the SAM material is too high, it is not conducive to improving the uniformity and stability of the subsequently formed perovskite layer.

[0032] In some embodiments, the solvent is at least one of isopropanol, ethanol and N,N-dimethylformamide. The above-listed solvents can dissolve the ligand reagent, facilitating uniform coating of the mixed solution on the metal oxide layer.

[0033] In some embodiments, in the mixed solution, the concentration of the ligand reagent is 1 to 10 mg / mL, for example, 1 mg / mL, 2 mg / mL, 4 mg / mL, 6 mg / mL, 8 mg / mL, 10 mg / mL, etc. When the concentration of the ligand reagent in the mixed solution is too low, it is not conducive to improving the adhesion between the conductive substrate, the metal oxide layer and the ligand-coupled SAM layer, nor is it conducive to improving the self-assembly uniformity of the ligand-coupled SAM layer. When the concentration of the ligand reagent in the mixed solution is too high, it is not conducive to reducing costs and increasing efficiency.

[0034] In some embodiments, in the mixed solution, the concentration of the SAM material is 1 to 10 mg / mL, such as 1 mg / mL, 2 mg / mL, 4 mg / mL, 6 mg / mL, 8 mg / mL, 10 mg / mL, etc. When the concentration of the SAM material in the mixed solution is too low, it is not conducive to improving the uniformity and stability of the subsequently formed perovskite layer. When the concentration of the SAM material in the mixed solution is too high, it is not conducive to improving the self-assembly uniformity of the ligand-coupled SAM layer.

[0035] In some embodiments, the holding temperature of the annealing treatment is 50 to 150°C, such as 50°C, 60°C, 80°C, 100°C, 120°C, 150°C, etc., and the holding time of the annealing treatment is 1 to 30 minutes, such as 1 minute, 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, etc. When the holding temperature of the annealing treatment is too low or the holding time is too short, it is not conducive to improving the crystallinity of the ligand-coupled SAM layer, thereby improving the charge transfer characteristics of the perovskite solar cell. When the holding temperature of the annealing treatment is too high or the holding time is too long, it is not conducive to reducing costs and increasing efficiency.

[0036] In some embodiments, the thickness of the ligand-coupled SAM layer is 10 to 30 nm, such as 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, etc. When the thickness of the ligand-coupled SAM layer is too small, it is not conducive to optimizing the interface between the metal oxide layer and the perovskite layer. When the thickness of the ligand-coupled SAM layer is too large, it is not conducive to improving the carrier transfer efficiency, thereby not being conducive to improving the photoelectric conversion efficiency of the perovskite solar cell.

[0037] The present invention is described in detail below with reference to embodiments.

[0038] Example 1

[0039] (1) A NiOx layer with a thickness of 200 nm was obtained by vapor deposition on the surface of the cleaned and dried ITO conductive glass.

[0040] (2) Dissolve the SAM material 2PACz in anhydrous ethanol, and then dissolve the ligand reagent 3-(1H-1,2,4-triazol-1-yl)benzoic acid (3-Hbza) in the above anhydrous ethanol to obtain a mixed solution, wherein the concentration of the SAM material 2PACz in the above mixed solution is 5 mg / mL, and the concentration of the ligand reagent 3-(1H-1,2,4-triazol-1-yl)benzoic acid (3-Hbza) in the above mixed solution is also 5 mg / mL.

[0041] The mixed solution is spin-coated onto the upper surface of the NiOx layer to obtain a wet film; the wet film is annealed to obtain a ligand-coupled SAM layer with a thickness of 20 nm; wherein the annealing temperature is 80° C. and the annealing time is 15 min.

[0042] (3) A perovskite CH3NH3PbI3 wet film is prepared on the upper surface of the ligand-coupled SAM layer by a one-step spin coating method, and the wet film is annealed to obtain a perovskite CH3NH3PbI3 layer with a thickness of 500 nm; wherein the annealing treatment is carried out at a holding temperature of 100°C and a holding time of 30 min.

[0043] (4) Prepare a 60nm thick C 60 layer.

[0044] (5) In the above C 60 A 60nm thick Au electrode is prepared on the upper surface of the layer to obtain a perovskite solar cell.

[0045] Example 2

[0046] This embodiment is the same as Example 1, except that 4-(1H-1,2,4-triazol-1-yl)benzoic acid (Hbza) is used in this embodiment instead of 3-(1H-1,2,4-triazol-1-yl)benzoic acid (3-Hbza) in Example 1, and the mass ratio of 4-(1H-1,2,4-triazol-1-yl)benzoic acid (Hbza) to 2PACz in this embodiment is 1:2.

[0047] Example 3

[0048] This example is the same as Example 1, except that this example uses HS-PEG-NH2 (thiol-polyethylene glycol-amino) instead of the siloxane in Example 1, and the mass ratio of HS-PEG-NH2 to 2PACz is 2:1.

[0049] Example 4

[0050] This embodiment is the same as Example 1, except that, in this embodiment, a combination of 3-(1H-1,2,4-triazol-1-yl)benzoic acid (3-Hbza) + 4-(1H-1,2,4-triazol-1-yl)benzoic acid (Hbza) in a mass ratio of 1:1 is used instead of 3-(1H-1,2,4-triazol-1-yl)benzoic acid (3-Hbza) in Example 1.

[0051] Example 5

[0052] This embodiment is the same as Example 1, except that this embodiment uses a combination of 3-(1H-1,2,4-triazol-1-yl)benzoic acid (3-Hbza) + HS-PEG-NH2 with a mass ratio of 1:1 instead of 3-(1H-1,2,4-triazol-1-yl)benzoic acid (3-Hbza) in Example 1.

[0053] Example 6

[0054] This embodiment is the same as Example 1, except that this embodiment uses a combination of 4-(1H-1,2,4-triazol-1-yl)benzoic acid (Hbza) + HS-PEG-NH2 with a mass ratio of 1:1 instead of 3-(1H-1,2,4-triazol-1-yl)benzoic acid (3-Hbza) in Example 1.

[0055] Example 7

[0056] This embodiment is the same as Example 1, except that this embodiment uses a combination of siloxane + 4-(1H-1,2,4-triazol-1-yl)benzoic acid (Hbza) + HS-PEG-NH2 with a mass ratio of 1:1:1 instead of 3-(1H-1,2,4-triazol-1-yl)benzoic acid (3-Hbza) in Example 1.

[0057] Comparative Example 1

[0058] This comparative example is the same as Example 1, except that no ligand reagent is added in step (2).

[0059] Comparative Example 2

[0060] This comparative example is the same as Example 1, except that the ligand-coupled SAM layer is replaced by a SAM layer, and a ligand-coupled perovskite layer is prepared on the SAM layer. The preparation method is as follows:

[0061] (1) A NiOx layer with a thickness of 200 nm was obtained by vapor deposition on the surface of the cleaned and dried ITO conductive glass.

[0062] (2) Dissolving the SAM material 2PACz in anhydrous ethanol to obtain a SAM solution, wherein the concentration of the SAM material 2PACz in the SAM solution is 5 mg / mL.

[0063] The SAM solution is spin-coated onto the upper surface of the NiOx layer to obtain a wet film; the wet film is annealed to obtain a SAM layer with a thickness of 20 nm; wherein the annealing temperature is 80° C. and the annealing time is 15 min.

[0064] (3) Adding a ligand reagent siloxane to the perovskite precursor solution, wherein the concentration of siloxane in the perovskite precursor solution is 5 mg / mL; preparing a ligand-coupled perovskite CH3NH3PbI3 wet film on the upper surface of the SAM layer by a one-step spin coating method, and annealing the wet film to obtain a ligand-coupled perovskite CH3NH3PbI3 layer with a thickness of 500 nm; wherein the annealing treatment is performed at a holding temperature of 100°C and a holding time of 30 min.

[0065] (4) Prepare a 60 nm thick C on the surface of the above ligand-coupled perovskite CH3NH3PbI3 layer 60 layer.

[0066] (5) In the above C 60 A 60nm thick Au electrode is prepared on the upper surface of the layer to obtain a perovskite solar cell.

[0067] Comparative Example 3

[0068] This comparative example is the same as comparative example 2, except that the ligand reagent is 4-(1H-1,2,4-triazol-1-yl)benzoic acid (Hbza).

[0069] Comparative Example 4

[0070] This comparative example is the same as comparative example 2, except that the ligand reagent is HS-PEG-NH2.

[0071] The photoelectric conversion efficiency of the perovskite solar cells of Examples 1 to 7 and Comparative Examples 1 to 4 was tested, and the test results are shown in Table 1.

[0072] Table 1. Photoelectric conversion efficiency of perovskite solar cells of Examples 1 to 7 and Comparative Examples 1 to 4

[0073]

[0074] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0075] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for treating a metal oxide layer-perovskite layer interface, characterized in that: The following steps are involved: S1. dissolving a ligand reagent and a SAM material into a solvent to obtain a mixed solution, wherein the ligand reagent has at least one of an -OH group, a -COOH group and a -NH2 group; S2. applying the mixed solution onto the surface of the metal oxide layer to obtain a wet film; S3. Annealing the wet film to obtain a ligand-coupled SAM layer.

2. The processing method according to claim 1, characterized in that: The ligand reagent is at least one of 4-(1H-1,2,4-triazol-1-yl)benzoic acid (Hbza), 3-(1H-1,2,4-triazol-1-yl)benzoic acid (3-Hbza) and thiol-polyethylene glycol-amino.

3. The processing method according to claim 1, characterized in that: The SAM material is at least one of 2PACz, Meo-2PACz and Me-4PACz.

4. The processing method according to claim 1, characterized in that: The mass ratio of the ligand reagent to the SAM material is 1:3 to 3:

1.

5. The processing method according to claim 1, characterized in that: The solvent is at least one of isopropanol, ethanol and N,N-dimethylformamide.

6. The processing method according to claim 1, characterized in that: In the mixed solution, the concentration of the ligand reagent is 1-10 mg / mL.

7. The processing method according to claim 1, characterized in that: In the mixed solution, the concentration of the SAM material is 1-10 mg / mL.

8. The processing method according to claim 1, characterized in that: The holding temperature of the annealing treatment is 50 to 150° C., and the holding time of the annealing treatment is 1 to 30 minutes.

9. The processing method according to claim 1, characterized in that: The thickness of the ligand-coupled SAM layer is 10-30 nm.

Citation Information

Patent Citations

  • Perovskite solar cell and preparation method thereof

    CN116940131A

  • Nitrogen heterocyclic organic compound and application thereof

    CN117164634A

  • All-inorganic CsPbIBr2 perovskite solar cell based on polyethylene glycol derivative modification and preparation method and application thereof

    CN117979711A

  • Method for optimizing NiOx / SAM hole transport layer of perovskite solar cell

    CN118555884A

  • Method for manufacturing perovskite solar cell

    CN118765146A